INFLUENCE OF FEEDBACK SEEKING FOR IMPROVEMENT AND LEARNING ENGAGEMENT TOWARDS ENTREPRENEURIAL PROJECT PERFORMANCE - Dwi Sunu Widyo Pebruanto; Norashidah Binti Hashim; Rosna Bt Awang Hashim (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2018)
Entrepreneurial education is not only applicable exclusively in business, but also in daily life. This research is focused on identifying the causal relationship between Feedback Seeking for Improvement (FSI) and Learning Engagement (LE) towards Entrepreneurial Project Performance as implemented in Ciputra Way Entrepreneurial Learning Model for middle school students. Results indicated Learning Engagement positively contributed towards Entrepreneurial Project Performance, meanwhile, Feedback Seeking Improvement shows negative contribution the same outcome variable.